Pengaruh Pendidikan dan Latihan Promosi serta Pemindahan Pegawai terhadap Prestasi Kerja pada Kantor Bapedda Litbang Kabupaten Kerinci - Alfero, M Rexsi; Lanin, Dasman (PUBLICNESS: Journal of Public Administration Studies, 2023)
This have a purpose to see the influence of education and training, promotion and transfer of staff By Bapedda R&D Kerinci Regency. For this type of research, namely Kuantitative. While The sampling technique used is total sampling. As for to population numbers employees who are in Bapedda R&D Kerinci Regency which amounts to 37 people. The results showed that (1) There is pengaruh education and practice towards work performance on Bapedda R&D of Kerinci Regency, bahwa found significance value that is 0,000 < 0.05. (2) There is pengaruh promotion towards work performance on Bapedda R&D of Kerinci Regency, that found significance value that is 0,000 < 0.05. (3) There is pengaruh employee transfers towards work performance on Bapedda R&D of Kerinci Regency that found significance value that is 0,000 < 0.05. (4) There is an influence education and practice, promotion and employee transfers towards work achievements in Bapedda R&D, Kerinci Regency found significance value that is 0.000 < 0.05.